Identifying Suitable Social Worker Candidates for Counselling Using Holland RIASEC Model and FIKR (Facet, Insight, Knowledge, Resilience) Profiling - Yap, Chee Kong; Leow, Chee Seng; Leong, Wing Sum Vincent (Asean Social Work Journal, 2025)
This study aimed to identify individuals best suited for counselling occupations using the Holland RIASEC Model and the FIKR (Facet, Insight, Knowledge, and Resilience) Profiling Assessment Tool. A total of 190 respondents were assessed, focusing on six personality dimensions—Realistic (R), Investigative (I), Artistic (A), Social (S), Enterprising (E), and Conventional (C). Results showed that 40 respondents (21.05%) were highly suitable for counselling roles, characterized by high Social scores, often paired with strong Investigative traits. Demographically, older female respondents demonstrated a slight advantage, suggesting that life experience may enhance counselling effectiveness. The study emphasizes the value of targeted training programs to further develop counselling competencies among identified individuals. These findings provide a foundation for selecting and developing candidates for counselling roles, ensuring they possess the necessary interpersonal and analytical skills. The research contributes to understanding career alignment and highlights the importance of personality assessment in professional development. By identifying individuals naturally inclined toward counselling, the study supports the creation of tailored training programs, benefiting educational institutions, employers, and policymakers involved in the recruitment and training of counselling professionals.